SAT0595 INTERSTITIAL LUNG DISEASE IN SOUTH AFRICAN ADULTS PATIENTS WITH AUTOIMMUNE RHEUMATIC DISEASES. (2nd June 2020) - Palalane, E.; Alpizar-Rodriguez, D.; Botha, S.; Said-Hartley, Q. M. S. H.; Calligaro, G.; Hodkinson, B.
Abstract : Background: Interstitial lung disease (ILD) is prevalent in patients with autoimmune rheumatic diseases (ARD), leads to significant morbidity and mortality, and is poorly characterized in South Africa. Objectives: To describe the clinical, serological and radiological features of ILD associated with ARD in a tertiary referral hospital. Methods: A cross-sectional study of outpatients attending the rheumatology and respiratory clinics of Groote Schuur Hospital between October 2018 and September 2019. Clinical, serological and radiological features were documented. We compared features of 3 groups of patients: rheumatoid arthritis (RA), systemic sclerosis (SSc) and "Other" autoimmune rheumatic diseases (OARD) which included Idiopathic Inflammatory Myopathies, Mixed Connective Tissue Disease, Systemic Lupus Erythematous, ANCA-associated vasculitis, Sjogren's Syndrome and overlap syndromes. Factors associated with Usual Interstitial Pneumonia (UIP) were sought by univariate and multivariate analysis. P-values ≤ 0.05 were considered statistically significant. Analyses was performed with STATA 14.0 (Stata Corp LP, USA). Results: Of 124 patients, 29.8 % had RA, 25, 8 % SSc and 44.4 % OARD. Most patients were female (86.3%), of mixed racial ancestry (75.0%), and the median (IQR) age was 55 (46-66). Over one-third were smokers, 22.6% had emphysema, and one third had previous pulmonary tuberculosis (PTB) infection. Smoking, emphysema, and previous PTB were higher in RA group but the difference was not statistically significant. All SSc patients and more than two-thirds of RA and OARD patients had gastroesophageal reflux disease (GORD). Similar to reports elsewhere, Nonspecific interstitial pneumonia (NSIP) was the commonest ILD (63.7 %), followed by UIP (26.6%) and other patterns (9.7%). Contrary to other reports, we found similar frequencies of NSIP and UIP patterns in patients with RA. RA patients were significantly older (median (IQR)) age at ILD onset 62 (55-68) years, compared to SSc (49 (38-56) and OARD (42 (33-56) (p < 0.001). The percentage of predicted Forced Vital Capacity (FVC) were significantly worse in SSc and OARD groups and DLCO in OARD. RA diagnosis (OR 3.8, 95% CI 1.5-9.5), older age (0R 1.1, 95% CI 1.0-1.1), COPD (OR 3.2, 95% CI 1.4-8.0), longer ARD-ILD interval, higher FVC (OR 1.0, 95% CI 1.0-1.1) and previous Methotrexate (MTX) use (OR 2.6, 95% CI 1.1-6.0) were significantly associated with UIP. Multivariable analysis showed that only COPD and previous MTX use was associated with UIP (OR 2.8 (95% CI 1.0 – 8.0) and 1.0 (95% CI 1.0 – 1.0) respectively). Regarding MTX exposure, 37.1% of patients were prescribed MTX before ILD diagnosis, and 33.9% continued, started or restarted after ILD diagnosis. No case of acute pneumonitis was documented. Conclusion: ILD was most commonly diagnosed in RA and SSc, with NSIP seen most frequently overall. RA patients presented better Pulmonary function tests despite higher frequency of UIP. The use of MTX seems to not be associated with the development of acute pneumonitis in patients with ILD References: [1]Wallace, B., D. Vummidi, and D. Khanna, Management of connective tissue diseases associated interstitial lung disease: a review of the published literature. Current Opinion in Rheumatology, 2016. 28 (3): p. 236-245. [2]Dellaripa, P.F., Interstitial lung disease in the connective tissue diseases; a paradigm shift in diagnosis and treatment. Clinical Immunology, 2018. 186 : p. 71-73. Disclosure of Interests: None declared